2008
DOI: 10.1107/s1744309108020186
|View full text |Cite
|
Sign up to set email alerts
|

Expression, purification and crystallization ofHelicobacter pyloriL-asparaginase

Abstract: The l-asparaginases from Escherichia coli and Erwinia chrysanthemi are effective drugs that have been used in the treatment of acute childhood lymphoblastic leukaemia for over 30 years. However, despite their therapeutic potential, they can cause serious side effects as a consequence of their intrinsic glutaminase activity, which leads to l-glutamine depletion in the blood. Consequently, new asparaginases with low glutaminase activity, fewer side effects and high activity towards l-asparagine are highly desira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…Recent reports have shown that Erwinia carotovora L-asparaginase (EwA) and two Helicobacter pylori LASNases have reduced (1.5%) [46] to negligible (0.01%) [47] glutaminase activities, respectively. Sequence comparison indicates that the active site is highly conserved between L-ASNases with only a few variations.…”
Section: Structural Basis Of Asparaginase-glutaminase Activity Ratiomentioning
confidence: 99%
“…Recent reports have shown that Erwinia carotovora L-asparaginase (EwA) and two Helicobacter pylori LASNases have reduced (1.5%) [46] to negligible (0.01%) [47] glutaminase activities, respectively. Sequence comparison indicates that the active site is highly conserved between L-ASNases with only a few variations.…”
Section: Structural Basis Of Asparaginase-glutaminase Activity Ratiomentioning
confidence: 99%
“…In addition to the biochemically well-characterized enzymes described above, PDB currently holds two structures of type II ASNase from H. pylori (HpA; PDB IDs 2wt4 and 2wlt) [59,108] and one structure of C. jejuni ASNase (CjA, PDB ID 3nxk, unpublished) (Table 4). Unfortunately, in neither case structural reports were complemented by activity/kinetic characteristics, limiting subsequent analysis.…”
Section: Pseudomonas 7a (Pga)mentioning
confidence: 99%
“…HpA was expressed and purified using ion-exchange chromatography as reported previously (Dhavala et al, 2008). Crystals were grown using the hanging-drop vapour-diffusion method at 289 K by mixing 2.5 ml enzyme solution (3.7 mg ml À1 in 10 mM HEPES-NaOH pH 7.0) with an equal volume of a reservoir solution consisting of 17.5%(w/v) PEG 4000, 0.1 M magnesium formate, 0.1 M HEPES-NaOH pH 7.0.…”
Section: Crystallization Conditionsmentioning
confidence: 99%